Factors influencing the development of management skills in South African civil engineers - Reddy, Premanathan (My University, 2011)
The objective of this research was to identify the factors, both the barriers and facilitators, influencing the development of management skills in South African civil engineers. There were 2 research propositions set up from the literature review. The research method adopted was quantitative factor analysis to test the two propositions. Data was collected through a survey conducted at a case site Grinaker-LTA. A 7-point Likert scale was used as the measuring instrument. The research findings concluded that the factors which are barriers in the development of management skills in civil engineers included the lack of training, the lack of management skills in engineers and job dissatisfaction. The facilitating factors included the use of coaching, management related training, the use of employee feedback systems and the self development of the engineer. The second research proposition produced two new factors which were the learning organisation and the effects of cultural diversity on the management development process of engineers. The key recommendations include that human resource managers in construction firms should use the factors from the research in order to improve the processes within the organisation in order to assist in the development of engineers into managers
MBA - WBS
Keywords: Management development; Engineers, Civil